Tanggung Jawab Perdata Pemborong Akibat Kegagalan Bangunan dalam Perspektif Hukum Positif Indonesia - I Ketut Suardika; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2021)
The collapse of several buildings as reported by various media including the collapse of the Yellow Bridge in Nusa Lembongan Klungkung, the collapse of Kutai Kartanegara Bridge, the collapse of the perimeter of Soekarno Hatta Airport, the collapse of the stock trading center building of the Indonesia Stock Exchange (IDX). For this event, the Contractor who participated in its construction should be held accountable. The collapse of buildings outside the force majeure in UUJK 2/2017 is referred to as Building Failure. KuhPerdata, UUJK 2/2017 on Construction Services and its derivative regulations are positive laws that are still valid (ius constitutum) as the legal umbrella in the implementation of development arrangements. In this paper, it intends to review legal issues resulting from building failure by analyzing the relevant legal provisions in the Civil Code and Law No. 2 of 2017.